Policy Support for Climate Risk Adaptation the Role of Microfinance - Sahat M. Pasaribu; Mat Syukur (Analisis Kebijakan Pertanian, 2010)
Agricultural development in Indonesia is being faced by the unpredictable climate situation. With such a high risk, however, Indonesia should be able to provide sufficient food for all of the people and access to food at affordable prices. In this regard, the climate field school is important to improve farmer’s konowledge to anticipate such climate change. While adapting to the climate change, agricultural activities should be protected and reduced the risk to the lowest possible level. Agricultural insurance is introduced to protect the farms, share the risk, and favor the farmers. Rice farm insurance, in particular, is applicable to share the risk of harvest failure caused by flood, drought and pest and disease infestations. Government support to provide subsidy for premium payment is encouraged. Such subsidy would be reduced gradually and integrated in the farm cost of production. In the absence of agricultural bank in Indonesia, microfinance institution is required to provide sufficient fund to cover cost of production. For a short-term follow up action, the current Rural Agribusiness Development Program (PUAP) is expected to help farmers through its microfinance institution in funding the farm activities. The role of microfinance is part of the climate change anticipation strategy and is very significant to help farmers to envisage the effect of harvest failure risk.